Chitosan Nanoparticle Based Mucosal Vaccines Delivered Against Infectious Diseases of Poultry and Pigs - Gourapura, Renukaradhya J.; Renu, Sankar (Frontiers in Bioengineering and Biotechnology, 2020)
Infectious diseases of poultry and pig are major threat to health and cause severe economic loss to the food industry and a global food safety issue. Poultry and pig act as a mixing vessel of zoonotic transmission of diseases to humans. Effective mucosal vaccines used in animals could reduce the impact of diseases in food animals. Chitosan is a biocompatible polymer, and its positive charge makes it a natural mucoadhesive agent. Therefore, since last one-decade chitosan derived nanoparticles (CS NPs) have been in use widely to deliver vaccine antigens in animals through mucosal route. Primary route of entry of most infectious disease pathogen is through oral and nasal routes, and the CS NPs based vaccines delivered through that routes enhance the immunogenicity of encapsulated vaccine antigens by targeting the cargo to mucosal microfold cells, dendritic cells and macrophages. Resulting in induction of robust secretory and systemic antibodies and/or cell mediated immune response which provides protection against infections. To date, CS NPs is being widely used for mucosal vaccine delivery in poultry and pigs to control bacterial and viral infections, and tested in several preclinical trials for vaccine delivery in humans. In this review, we highlighted the progress so far made in using CS NPs as a vehicle for mucosal vaccine delivery against infectious and zoonotic diseases of poultry and pigs. Discussed about the need of CS NPs modifications, CS NPs based vaccines induced immune response and its role in protection, and challenges in vaccination and future directions.